REVISION OF SOLANUM SECTION REGMANDRA (SOLANACEAE) - Bennett, J. R. (Edinburgh Journal of Botany, 2008)
Solanum section Regmandra (Solanaceae), a group of 11 species from the lomas of Chile and Peru, is revised. Two new species are described, Solanum indivisum Witasek ex J.R.Benn. and S. coquimbense J.R.Benn., and a new name, S. trinominum J.R.Benn., is proposed for S. heterantherum Witasek ex Reiche. Two species, Solanum multifidum Lam. and S. edmonstonei Hook.f., are endemic to Peru, seven species are endemic to Chile, and only two species are found in both countries. Descriptions, distribution maps and a key to the species are presented and several species illustrated.
Keywords: Chile; lomas; Peru; Solanaceae; Solanum section Regmandra; species delimitation; taxonomy